RECENT BLOOMING OF PYRODINIUM BAHAMENSE VAR. COMPRESSUM IN AMBON BAY, EASTERN INDONESIA - Likumahua, Sem (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2013)
In Indonesia, Pyrodinium bahamense var. compressum was first recorded in Kao Bay in 1994. In 1996 the illness of more than 30 people and the death of 3 children after consuming shellfish from Ambon Bay was reported. Until the shellfish poisoning cases was reported, occurrences and blooms of P. bahamense, neither its toxic events had never been known in Ambon Bay. It has generated monitoring on the species occurrence which has been carried out since 2008. The bloom of P. bahamense was detected in July 2012. During the bloom event, concentrationsof phosphate, nitrate and dissolved oxygen were measured. Vertical profiles of temperature, salinity, turbidity and chlorophyll a were also measured during the red tide. Cells of P. bahamense, the PSP responsible species, were recorded abundant up to 2,496 cells/ml when red-brown water discoloration was observed in Ambon Bay. After the toxic red tide, human illness of 7 people due to shellfish consumption was also reported. In addition, the bloom event has damaged aquaculture products, due to mass mortality of cultured fish in inner Ambon Bay.